The Tradition of Marriage and Dowry Extension in Islamic Marriage: Between Legal Sharia and Local Culture of the Archipelago - Kholis Firmansyah; Athal Izdihar Parkash; Jovita Dwi Kusumastuti; Nabhan Tabarok; Meylin Yunda Safira; Hannamuddin Wafiyur Rahman (PT. Nawa Edukasi Nusantara, 2026)
This extensive and comprehensive study explores the dynamic intersection between Islamic marriage jurisprudence (Fiqh Munakahat) and local cultural practices in Indonesia, focusing deeply on the traditions of proposing (Khitbah), the rigorous pillars and conditions of marriage, the provision of dowry (Mahar), and the strict marriage prohibitions. Marriage in Islam is a sacred covenant aimed at building a harmonious family, governed by precise jurisprudential rules to ensure its legal, social, and theological validity. However, the implementation of these rules in Indonesia is heavily influenced by diverse customary practices ('Urf). The research aims to critically analyze how local traditions align or conflict with classical Islamic jurisprudence. Using a qualitative library research method integrated with a socio-legal approach, the study evaluates primary Islamic texts, the Indonesian Marriage Law, the Compilation of Islamic Law, and extensive ethnographic literature. The findings prominently reveal that while many local customs serve as valid customs ('Urf Shahih) that complement Islamic law by emphasizing social harmony and family integration, certain practices bordering on extravagance and excessive material demands create severe socio-economic burdens. The paper concludes that a harmonization approach is essential, ensuring that customary practices enrich the marital process without violating the fundamental principles of Islamic jurisprudence, specifically the principles of facilitation (taisir) and the preservation of human dignity.